Finding a suitable fit function used to determine the Physical width of the Flux tube with Dynamical fermions - Purev, Battogtokh; Chagdaa, Sodbileg; Galsandorj, Enkhtuya (Proceedings of the Mongolian Academy of Sciences, 2020)
We have determined the width of the flux tube for several temperatures and distances using four different fit functions in order to determine the appropriate function that fits the data of the middle transverse distribution of flux tube with the dynamical fermions. Our results have revealed that only one fitting function cannot determine the width of the flux tube at the given temperatures and distances. We conclude that appropriate fit functions are a four coefficient function where R < 0.8 fm and where Gaussian function is R > 0.8 fm.